Experimental study of drying characteristics and mathematical modeling for air drying of germinated brown rice - Yu, Zhenwei; Yousaf, Khurram; Wang, Yu; Chen, Kunjie (Penerbit Universiti Kebangsaan Malaysia, 2019)
In view of existing problems in the drying process of germinated brown rice (GBR), the self-made hot air drying test system was utilized. The drying medium temperature and wind speed were selected as the drying parameters, and different constraints were set for the test. The effects of the drying medium temperature and wind speed on the drying rate and unit energy consumption were examined, and the drying mathematical models of GBR were established. The results perceived that as the temperature rose, and the wind speed increased, the drying rate increased accordingly. When the temperature was above 95°C, wind speed exceeded 3.6 m/s; the drying rate would not change deliberately. When the temperature of the drying medium rose, the change rate during the drying preheating stage and the deceleration stage increased sharply, whereas the drying rate in the constant-speed drying stage increased, and the drying time was greatly shortened. Unit energy consumption decreased with the increase of temperature and increased with increasing wind speed. Furthermore, when the drying temperature was ranged between 50°C and 80°C, the unit energy consumption changed meaningfully; when the medium temperature was between 80°C and 110°C, the unit heat consumption turned slowly. Wang and Singh’s model could best simulate the drying process of GBR within the experimental settings. And then comparing the RMSE and under the various dry conditions, the data of Wang and Singh model were between 1.6% - 2.8% and 2.5×10-4 - 5×10-4. The R2 values of the model were higher than 0.98.